2013
DOI: 10.1002/pd.4219
|View full text |Cite
|
Sign up to set email alerts
|

Identification of interleukin‐1 beta, but no other inflammatory proteins, as an early onset pre‐eclampsia biomarker in first trimester serum by bead‐based multiplexed immunoassays

Abstract: This study indicates that IL-1β has potential to improve first trimester prediction of pre-eclampsia. Studies on larger cohorts will be needed to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…IL-1b, a key inflammatory factor, is highly expressed in PE patients [36,37,44]. In this study, we found that miR-30a could regulate the immunosuppressive function of IL-1b-elicited MSCs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…IL-1b, a key inflammatory factor, is highly expressed in PE patients [36,37,44]. In this study, we found that miR-30a could regulate the immunosuppressive function of IL-1b-elicited MSCs.…”
Section: Discussionmentioning
confidence: 61%
“…IL-1b, a crucial soluble inflammatory mediator, can enhance the immunosuppressive functions of MSCs and induce their production of IL-6, COX2 and IL-8 [34,35]. Importantly, the up-regulation of IL-1b expression was observed in PE patients [36,37]. To investigate the effects of miR-30a on the immunoregulatory activities of MSCs, IL-1b was used to stimulate the transfected MSCs.…”
Section: Over-expressed Mir-30a Suppresses the Immunosuppressive Actimentioning
confidence: 99%
“…A limitation of this study is the relatively small number of cases, but we find these numbers to be comparable to previous casecontrol studies investigating serum cytokines in hypertensive pregnancy disorders, 33,34,53 and our study includes a larger control group. Because our medium-to high-risk cohort predominantly included women developing late-onset gestational hypertension or preeclampsia, the findings presented here should be followed-up in a general pregnant population with larger groups, including early-and late-onset disease.…”
Section: Downloaded Frommentioning
confidence: 78%
“…28,29 A first trimester study by Wolf et al concluded that inflammatory activation, assessed by high-sensitivity C-reactive protein measurements, was not associated with gestational hypertension, 44 but our somewhat contradictory findings result from a more comprehensive cytokine profiling approach. For preeclampsia, serum cytokine profiling has previously shown results ranging from elevated first trimester IL-1β levels predicting early onset disease 34 to no cytokine differences before clinical manifestation of early or late onset preeclampsia. 45,46 We did not find any such differences in our cohort of late onset preeclampsia compared with normotensive pregnancies.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation